Pengaruh Audit Jarak Jauh (Remote Audit) Dan Jumlah Penugasan Auditor Terhadap Kualitas Audit - Okta Putri, Rizka; Dwiharyadi, Anda; Chandra, Novrina (Akuntansi dan Manajemen, 2024)
This research aims to determine the effect of remote audits and the number of auditor assignments on audit quality, moderated by audit information technology and professional development (empirical study on BPKP representatives in West Sumatra Province). The population in this study was 95 people with a sample of 95 respondents. The type of data in this research is quantitative data. Data was obtained by conducting a questionnaire, then processed and tested using SmartPLS. The data analysis method used is descriptive analysis, quality testing (data normality), confirmatory test (validity test, reliability test, model suitability test results (goodness of fit test) and hypothesis testing. From the research conducted it is known that based on the results of hypothesis testing it shows that Remote audit and audit assignments have a positive and significant effect on audit quality, Professional Development has no mediation between Audit Assignments and audit quality, Professional Development has mediation between remote audits and audit quality, Information Technology has no mediation between Audit Assignments and audit quality and Information Technology has mediation between remote audit and audit quality.